Preparation method and application of polyoxometallic acid etching optimized nickel molybdate oxygen evolution electrocatalytic material

By synthesizing and etching nickel molybdate nanorods in situ on nickel foam, the formation of polymetallic acid etching optimized nickel molybdate oxygen evolution electrocatalytic material was solved, and the problem of insufficient electron conductivity and structural stability in the electrocatalytic water decomposition of NiMoO4 electrodes was achieved, and efficient oxygen evolution reaction and long-term stability were achieved.

CN119776879AActive Publication Date: 2025-04-08GUANGXI UNIV FOR NATITIES

Patent Information

Application Number
CN202411979718.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing NiMoO4 electrodes are limited by problems such as electron conductivity, insufficient ion transport and diffusion, and structural instability in electrocatalytic water decomposition, making it difficult to achieve efficient oxygen evolution reactions.

Method used

Flower clustered nickel molybdate nanorods were synthesized in situ on nickel foam by a one-step hydrothermal synthesis method, and placed them in a mixed solution of ethanol and water, and phosphotungstic acid and phosphodymium were added for etching, optimizing the structure and surface characteristics of nickel molybdate, forming a polymetallic acid etching optimized nickel molybdate oxygen evolution electrocatalytic material.

Benefits of technology

It significantly improves the oxygen evolution reaction performance of nickel molybdate, improves the charge transfer efficiency, reduces the charge transfer impedance, enhances the conductivity and chemical stability, realizes an efficient electrocatalytic oxygen evolution reaction, and maintains stability for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776879A_ABST
    Figure CN119776879A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrocatalytic materials, in particular to a preparation method and application of a polyoxometallic acid etching optimized nickel molybdate oxygen evolution electrocatalytic material. The preparation method comprises the following steps: putting flower-cluster-shaped nickel molybdate nanorods which are synthesized on foamed nickel in situ by a one-step hydrothermal synthesis method into a mixed solution of ethanol, water and polyoxometallic acid for etching, washing and drying to obtain the polyoxometallic acid etching optimized nickel molybdate oxygen evolution electro-catalytic material. According to the preparation method, the oxygen evolution reaction performance of the binary nickel-based material nickel molybdate is greatly improved, and the stability of a catalytic material can be guaranteed while efficient electro-catalysis oxygen evolution reaction is achieved. The prepared polyoxometallic acid etching optimized nickel molybdate oxygen evolution electro-catalytic material can be directly used as a self-supporting electrode for an electro-catalytic oxygen evolution reaction, and the method is simple in technological process, green, environmentally friendly, low in cost and low in production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic materials, and in particular to a preparation method and application of a polymetallic oxoacid-etched optimized nickel molybdate oxygen evolution electrocatalytic material. Background Art

[0002] Electrocatalytic water splitting (2H2O→O2+2H2) is an efficient and sustainable method for hydrogen production, which is expected to solve the energy crisis and environmental problems caused by traditional fossil fuels. The electrocatalyst hydrogen evolution reaction (HER) is a two-electron-proton coupling reaction, while the oxygen evolution reaction (OER) is a four-electron-proton coupling reaction. The reaction requires higher energy to overcome the energy barrier of the oxygen evolution reaction. Therefore, OER is usually considered to be the decisive step of the water splitting reaction, which can greatly reduce the efficiency of the electrochemical water splitting reaction. In order to overcome the influence of the OER process on the electrochemical water splitting process, it is crucial to select a suitable catalyst. Therefore, it is urgent to develop high-performance electrocatalysts that accelerate the kinetics of the oxygen evolution reaction.

[0003] Currently, the most commonly used anode catalysts are precious metal oxides, such as RiO2 and RuO2, which are the most widely used anode catalysts, but their high cost and low reserves hinder their practical application. Transition metal oxides have low cost, high reserves and good OER catalytic activity. Many groups are developing them as substitutes for OER electrocatalysts. Optimization methods include interface engineering, defect engineering, and metal doping to improve the OER performance of transition metal oxides (TMOs). Among transition metal-based compounds, binary nickel-based materials have been widely developed as efficient water splitting electrocatalysts, especially NiMoO4, which is currently the most studied nickel-based electrocatalyst, mainly due to the synergistic effect of the excellent water dissociation ability of Ni atoms and the excellent H2 adsorption ability of Mo atoms.

[0004] However, NiMoO4 electrodes are still affected by their poor electronic conductivity, insufficient ion transport and diffusion, and structural instability during long-term cycling. Therefore, it is very meaningful and challenging to controllably fabricate NiMoO4 with nano-microstructures and rationally design structural engineering. Specifically, various low-dimensional NiMoO4 nanostructures are directly grown on conductive current collector substrates (e.g., Ni / Cu foams, graphene, and carbon substrates), which reduce charge carrier scattering at grain boundaries and are easily integrated into flexible devices with certain specific applications, which are particularly preferred for directional electron transport. In order to overcome the poor conductivity of pure NiMoO4, various NiMoO4 / carbon composites have been synthesized by combining NiMoO4 nanostructures with graphene, carbon nanotubes, conductive polymers, and porous carbon structures. In addition to carbon composites, some people have tried to dope NiMoO4 with several heteroatoms (such as Mn, P, Zn, Ce), or to generate oxygen vacancies in the NiMoO4 lattice. In addition, NiMoO4 is also composited with other metal oxides or sulfides to form heterostructure electrodes to improve electrochemical performance. However, monotonous strategies sometimes have limited contributions to improving the overall electrochemical performance of NiMoO4 materials, and some reported composite or doping methods of NiMoO4 involve multiple complex chemical and physical processes, and the synthesis routes are economically costly or environmentally unfriendly.

[0005] Therefore, finding a low-cost, convenient and fast method to significantly improve the performance of oxygen evolution reaction and hydrogen evolution reaction of nickel molybdate materials in transition metal oxides has research value and application prospects. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material, which greatly improves the oxygen evolution reaction performance of the binary nickel-based material nickel molybdate, while achieving a high-efficiency electrocatalytic oxygen evolution reaction and ensuring the stability of the catalytic material.

[0007] The preparation method comprises the following steps: etching the flower-cluster nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method in a mixed solution of ethanol, water and polyoxometallic acid, washing and drying to obtain a polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material; the polyoxometallic acid comprises phosphotungstic acid and phosphomolybdic acid.

[0008] In some embodiments, the sum of the amounts of phosphotungstic acid and phosphomolybdic acid in 1 L of the mixed solution does not exceed 10 mmol.

[0009] In some embodiments, the volume ratio of ethanol to water is 1:4 to 4:1.

[0010] In some embodiments, the etching time is 15 to 90 minutes.

[0011] In some embodiments, washing is performed by first washing with anhydrous ethanol for 3 to 5 times, and then washing with deionized water for 3 to 5 times.

[0012] In some embodiments, the drying temperature is 50-60°C.

[0013] In some embodiments, the preparation method of in-situ synthesis of flower cluster-shaped nickel molybdate nanorods on nickel foam by a one-step hydrothermal synthesis method is specifically as follows: block nickel foam is ultrasonically treated in a mixed solution of hydrochloric acid, ethanol and water for 10 minutes, washed with ethanol and pure water for 2 to 3 times respectively, put into a polytetrafluoroethylene reactor containing a mixed solution of ammonium molybdate tetrahydrate and nickel nitrate hexahydrate, and then reacted at 150°C for 6 hours. After cooling to room temperature, the mixture is washed with ethanol and deionized water three times respectively, and finally dried at 60°C for 10 hours to obtain flower cluster-shaped nickel molybdate nanorods.

[0014] In some embodiments, the concentration of hydrochloric acid is 12 M, and the volume ratio of hydrochloric acid, ethanol and water is 1:1:1.

[0015] In some embodiments, the concentration of ammonium molybdate tetrahydrate is 15 mM, and the concentration of nickel nitrate hexahydrate is 35 mM.

[0016] In the preparation method of any of the above embodiments, the polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material can be cut into a suitable size according to actual conditions before use.

[0017] The present invention also provides the use of the polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material obtained by the above-mentioned preparation method in electrocatalytic electrolysis of water.

[0018] Specifically, the polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material obtained above was used as a working electrode to assemble into a three-electrode test system, the counter electrode was a graphite rod electrode, and the reference electrode was Hg / HgO.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention synthesizes nickel molybdate nanorods on nickel foam by a one-step hydrothermal synthesis method. In a mixed solution of ethanol and water, phosphotungstic acid and phosphomolybdic acid are used to etch the nano-flower cluster-shaped nickel molybdate nanorods grown in situ on the nickel foam to obtain an optimized nickel molybdate electrocatalytic material with improved charge transfer efficiency and reduced charge transfer impedance. The material has good electrical conductivity, is convenient for electron transfer, and has good chemical stability and structural stability. The material can be directly used as a self-supporting electrode for electrocatalytic oxygen evolution reaction. The method has a simple process, is green and environmentally friendly, and has low cost and production cost.

[0021] (2) The preparation method uses polyoxometallic acid to etch nickel molybdate nanorods, resulting in the lack of cations (Ni and Mo), changes in the lattice structure, and the formation of a small amount of oxygen vacancies while constructing metal defects; polyoxometallic acid etching of NMO@NF adds n(PO4) on its surface 3- , which will adjust its electronic properties. The enhanced edge structure has a strong attraction to the -OH group of the electrolyte, and the structural change produces excellent electrochemical behavior; metal oxoacid etching increases the valence state of Ni ions in NMO@NF. The increase in the valence state of Ni ions is conducive to the formation of NiOOH in the OER process and enhances the catalytic activity of OER.

[0022] (3) The prepared polyoxometalate-etched optimized nickel molybdate oxygen evolution electrocatalytic material electrode has excellent electrocatalytic oxygen evolution activity and stability. By exploring its electrocatalytic oxygen evolution reaction activity in 1 mol / L KOH electrolyte, the results show that the current density of PTA&PMA / NMO@NF is 10 mA / cm 2 The overpotential is only 200 mV, and the minimum Tafel slope is 32.8 mV / dec, indicating that the catalyst has good reaction kinetics; after 24 hours of current-time test, the electrode maintained good stability, the overpotential basically did not change, showing excellent stability.

[0023] (4) The prepared polyoxometalate etched optimized nickel molybdate oxygen evolution electrocatalytic material not only has excellent electrocatalytic oxygen evolution activity and stability, but also has good electrocatalytic hydrogen evolution activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : X-ray diffraction spectra of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1.

[0025] Figure 2 : Rnman spectra of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1.

[0026] Figure 3 : Scanning electron micrographs of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1, wherein (a) is a scanning electron micrograph of NMO@NF before etching, and (b) is a scanning electron micrograph of PTA&PMA / NMO@NF after etching.

[0027] Figure 4 : Transmission electron micrographs of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1, wherein (a) is a transmission electron micrograph of NMO@NF before etching, and (b) is a transmission electron micrograph of PTA&PMA / NMO@NF after etching.

[0028] Figure 5 : High-resolution transmission electron microscopy images of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1, wherein (a) is a high-resolution transmission electron microscopy image of NMO@NF before etching, and (b) is a high-resolution transmission electron microscopy image of PTA&PMA / NMO@NF after etching.

[0029] Figure 6 : EDX mapping of PTA&PMA / NMO@NF prepared in Example 1.

[0030] Figure 7 : Ni 2p X-ray high-resolution energy spectra of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1.

[0031] Figure 8 : Mo 3d X-ray high-resolution energy spectra of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1.

[0032] Fig. 9 : O1s X-ray high-resolution energy spectra of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1.

[0033] Fig.10 : Linear scanning curves of oxygen evolution reaction of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1 as electrocatalysts in 1M KOH electrolyte.

[0034] Fig.11 : Tafel plots of oxygen evolution reaction of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1 as electrocatalysts in 1M KOH electrolyte.

[0035] Fig.12 : AC impedance curves of oxygen evolution reaction of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1 as electrocatalysts in 1M KOH electrolyte.

[0036] Fig.13 : 24-hour stability graph of the oxygen evolution reaction current-time of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1 as electrocatalysts in 1 M KOH electrolyte.

[0037] Fig.14 : Linear scanning curves of hydrogen evolution reaction of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1 as electrocatalysts in 1M KOH electrolyte.

[0038] Fig.15: Tafel plots of hydrogen evolution reaction of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1 as electrocatalysts in 1M KOH electrolyte.

[0039] Fig.16 : AC impedance curves of hydrogen evolution reaction of NMO@NF and PTA&PMA / NMO@NF prepared in Example 1 as electrocatalysts in 1M KOH electrolyte. DETAILED DESCRIPTION

[0040] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art.

[0041] Example 1

[0042] (1) Flower-like nickel molybdate nanorods synthesized in situ on nickel foam by one-step hydrothermal synthesis: Commercial block nickel foam (NF) was cut into small pieces (1.0 cm*1.5 cm), ultrasonically treated in a mixed solution of hydrochloric acid (12.0 mol / L), ethanol and water in a volume ratio of 1:1:1 for 10 min, washed three times with ethanol and pure water respectively, and the surface moisture was dried with filter paper. 139 mg of ammonium molybdate tetrahydrate and 76 mg of nickel nitrate hexahydrate were ultrasonically dissolved in 7.5 mL of deionized water for 30 minutes and added to a polytetrafluoroethylene reactor (25.0 mL), and then a piece of pretreated nickel foam was placed in the reactor, and then heated in an air drying oven at 150 ° C for 6 h. After cooling to room temperature, it was washed three times with ethanol and deionized water respectively, and finally dried at 60 ° C for 10 h to obtain flower-like nickel molybdate nanorods (NMO@NF).

[0043] (2) Prepare 10 mL of a mixed solution of ethanol and deionized water (ethanol: water = 2:1) containing 115.2 mg of phosphotungstic acid (PTA) and 18.3 mg of phosphomolybdic acid (PMA), and then put the cluster-shaped nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method into the mixed solution for etching for 15 min. After etching, take out the nanorods, wash them three times with ethanol and deionized water respectively, and dry them in an oven at 60°C to obtain a polyoxometalate etching optimized nickel molybdate oxygen evolution electrocatalytic material (PTA&PMA / NMO@NF).

[0044] X-ray diffraction of NMO@NF and PTA&PMA / NMO@NF before and after etching was performed, and the comparison with the standard spectrum showed that NMO@NF was successfully synthesized. Figure 1 It can be seen that the lattice constant and volume increase slightly after etching.

[0045] The NMO@NF and PTA&PMA / NMO@NF before and after etching were characterized by Rnman. Figure 2 It can be seen that the Raman spectrum shifts to higher frequencies, indicating the generation of cation defects and changes in the lattice after etching.

[0046] The NMO@NF and PTA&PMA / NMO@NF before and after etching were scanned by electron microscope. Figure 3 It can be seen that the NFs are almost completely covered by flower-like clusters composed of NMO nanorods before etching, and there is no obvious change in the overall morphology after etching.

[0047] The NMO@NF and PTA&PMA / NMO@NF before and after etching were scanned by transmission electron microscope. Figure 4 , proving that metal precipitates after etching, the surface area becomes loose and defects occur.

[0048] The NMO@NF and PTA&PMA / NMO@NF before and after etching were scanned by high-resolution transmission electron microscopy. Figure 5 , indicating that there is some lattice distortion at the interface due to the precipitation of two cations (Ni and Mo) during the etching process.

[0049] PTA&PMA / NMO@NF is mapped using EDX. Figure 6 , indicating that Ni, Mo, O, P and W are uniformly distributed.

[0050] The NMO@NF and PTA&PMA / NMO@NF before and after etching were irradiated with X-rays. Figure 7 Ni 2p、 Figure 8 Mo 3d and Fig. 9 The high-resolution spectrum of O 1s confirms the existence of Ni, Mo, and O atoms, and also confirms the change of Ni atomic valence state before and after Ni molybdate etching. 3+ The ion ratio increased significantly.

[0051] Example 2

[0052] Step (1) of this embodiment is the same as that of Example 1, and step (2) is as follows:

[0053] 10 mL of a mixed solution of ethanol and deionized water (ethanol: water = 1:1) containing 115.2 mg of phosphotungstic acid (PTA) and 18.3 mg of phosphomolybdic acid (PMA) was prepared, and then the cluster-shaped nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method were placed in the mixed solution and etched for 15 minutes. After the etching was completed, the nanorods were taken out, washed with ethanol for 3 times, then washed with deionized water for 4 times, and dried in an oven at 50°C to obtain a polyoxometallic acid etching-optimized nickel molybdate oxygen evolution electrocatalytic material.

[0054] Example 3

[0055] Step (1) of this embodiment is the same as that of Example 1, and step (2) is as follows:

[0056] 10 mL of a mixed solution of ethanol and deionized water (ethanol: water = 3:1) containing 72 mg of phosphotungstic acid (PTA) and 45.6 mg of phosphomolybdic acid (PMA) was prepared, and then the flower cluster-shaped nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method were placed in the mixed solution and etched for 90 minutes. After etching, the nanorods were taken out, washed with ethanol and deionized water for 5 times respectively, and dried in an oven at 55°C to obtain a polyoxometallic acid etching-optimized nickel molybdate oxygen evolution electrocatalytic material.

[0057] Example 4

[0058] Step (1) of this embodiment is the same as that of Example 1, and step (2) is as follows:

[0059] 10 mL of a mixed solution of ethanol and deionized water (ethanol: water = 4:1) containing 115.2 mg of phosphotungstic acid (PTA) and 18.3 mg of phosphomolybdic acid (PMA) was prepared, and then the flower cluster-shaped nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method were placed in the mixed solution and etched for 60 minutes. After the etching was completed, the nanorods were taken out, washed with ethanol and deionized water for 4 times respectively, and dried in an oven at 60°C to obtain a polyoxometallic acid etching-optimized nickel molybdate oxygen evolution electrocatalytic material.

[0060] Example 5

[0061] Step (1) of this embodiment is the same as that of Example 1, and step (2) is as follows:

[0062] 10 mL of a mixed solution of ethanol and deionized water (ethanol: water = 1:4) containing 28.8 mg of phosphotungstic acid (PTA) and 73.2 mg of phosphomolybdic acid (PMA) was prepared, and then the flower cluster-shaped nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method were placed in the mixed solution and etched for 80 minutes. After the etching was completed, the nanorods were taken out, washed with ethanol for 4 times, then washed with deionized water for 3 times, and dried in an oven at 55°C to obtain a polyoxometallic acid etching-optimized nickel molybdate oxygen evolution electrocatalytic material.

[0063] Example 6

[0064] Step (1) of this embodiment is the same as that of Example 1, and step (2) is as follows:

[0065] 10 mL of a mixed solution of ethanol and deionized water (ethanol: water = 1:2) containing 2.88 mg of phosphotungstic acid (PTA) and 164.25 mg of phosphomolybdic acid (PMA) was prepared, and then the cluster-shaped nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method were placed in the mixed solution and etched for 70 minutes. After the etching was completed, the nanorods were taken out, washed with ethanol for 3 times, then washed with deionized water for 5 times, and dried in an oven at 55°C to obtain a polyoxometallic acid etching-optimized nickel molybdate oxygen evolution electrocatalytic material.

[0066] Example 7

[0067] Step (1) of this embodiment is the same as that of Example 1, and step (2) is as follows:

[0068] 10 mL of a mixed solution of ethanol and deionized water (ethanol: water = 1:3) containing 2.88 mg of phosphotungstic acid (PTA) and 1.64 mg of phosphomolybdic acid (PMA) was prepared, and then the cluster-shaped nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method were placed in the mixed solution and etched for 30 minutes. After etching, the nanorods were taken out, washed with ethanol for 3 times, then washed with deionized water for 3 times, and dried in an oven at 55°C to obtain a polyoxometallic acid etching-optimized nickel molybdate oxygen evolution electrocatalytic material.

[0069] Experimental Example 1 Electrochemical Performance Test

[0070] 1. Test method:

[0071] All electrochemical data were acquired using a CHI 660E electrochemical workstation equipped with a three-electrode system.

[0072] The prepared catalyst was loaded on NF as the working electrode, and the Hg / HgO electrode and graphite electrode were used as the reference electrode and counter electrode, respectively. The geometric area of ​​the working electrode immersed in the electrolyte was 1.0 cm × 1.0 cm. All potentials tested under the Hg / HgO electrode were calibrated to the potential under the reversible hydrogen electrode (RHE), and the oxygen evolution reaction (OER) test was carried out in 1M KOH solution at a scan rate of 5mv / s in the voltage range of 0-1.0V using the linear sweep voltammetry (LSV).

[0073] The Tafel slope of the sample was linearly fitted according to the Tafel equation (η=b log j+a, where η is the overpotential, b is the Tafel slope, and j is the current density).

[0074] Electrochemical impedance spectroscopy (EIS) was used to measure the electrolyte resistance R of different catalysts in the range of 10kHz to 0.01Hz. s and the charge transfer resistance R ct , and its 24-hour stability was measured using chronoamperometry.

[0075] The NMO@NF prepared in Example 1 and the etching-optimized PTA&PMA / NMO@NF were cut into a size of 1 cm×1 cm and tested as working electrodes.

[0076] 2. Test results:

[0077] Figure 10-13 This is the data diagram of electrocatalytic oxygen evolution of NiMoO4@NF prepared in Example 1 before and after etching treatment as an electrocatalyst in 1M KOH electrolyte.

[0078] Fig.10 and Fig.11 The overpotential of PTA&PMA / NMO@NF was significantly reduced, achieving 10 mA / cm at only 200 mV. 2 The current density was 100mA / cm at only 230mV. 2 NMO@NF requires an overpotential of 227 mV to achieve a current density of 10 mA / cm 2 The current density of 100mA / cm can be achieved at an overpotential of 267mV. 2 In addition, the Tafel slope of PTA&PMA / NMO@NF is 29.4 mV / dec, which is significantly lower than that of NMO@NF (44.2 mV / dec), indicating that the reaction kinetics of PTA&PMA / NMO@NF is good and more conducive to catalytic reaction.

[0079] Depend on Fig.12 , the charge transfer resistance (R ct ) is 1.5Ω, which is significantly lower than the charge transfer resistance of NMO@NF (3.7Ω). Therefore, the PTA&PMA / NMO@NF electrode has better conductivity and faster electron transfer rate.

[0080] Depend on Fig.13 After 24 hours of current stability test, the curve remained basically stable and the overpotential remained basically unchanged, proving that PTA&PMA / NMO@NF has outstanding electrochemical stability in the electrochemical process of oxygen evolution reaction.

[0081] Figure 14-16 This is the data diagram of electrocatalytic hydrogen evolution of NiMoO4@NF prepared in Example 1 before and after etching as an electrocatalyst in 1M KOH electrolyte.

[0082] Fig.14 Display, NMO / NF at 10mA / cm 2The highest overpotential of 167 mV was shown at 10 mA / cm 2 The overpotential is 119 mV, which is significantly lower than that of NMO / NF, indicating that the etching performance improvement significantly improves the activity of hydrogen evolution reaction.

[0083] Fig.15 It shows that the Tafel slope value of PTA&PMA / NMO@NF is 113.2 mV / dec, which is lower than the slope value of NMO@NF (180.0 mV / dec), indicating that PTA&PMA / NMO@NF has better hydrogen evolution reaction kinetics than NMO@NF, and the catalytic material modified by etching with phosphotungstic acid and phosphomolybdic acid is very beneficial to the HER reaction.

[0084] Fig.16 It is shown that the charge transfer resistance (R ct ) is 3.7Ω, which is significantly lower than the charge transfer resistance of NMO@NF (6.4Ω), indicating that the PTA&PMA / NMO@NF electrode also has better conductivity and faster reaction kinetics in the hydrogen evolution reaction.

[0085] Table 1 shows the performance comparison of OER with other electrocatalysts using 1M KOH as the electrolyte. The lowest overpotential of PTA&PMA / NMO@NF is 200mV, and the Tafel slope is 32.8mV / dec. It can be seen that the OER activity of PTA&PMA / NMO@NF is better than most transition metal catalysts reported previously.

[0086] Table 1

[0087]

[0088] (1)Jiang, R.; Zhao, D.; Fan, H.;

[0089] (2)Xie,W.;Huang,J.;Huang,L.;Geng,S.;Song,S.;Tsiakaras,P.;Wang,Y.,Novelfluorine-doped cobalt molybdate nanosheets with enriched oxygen-vacancies for improved oxygenevolution reaction activity.Applied Catalysis B:Environmental 2022,303,120871.

[0090] (3)Jiang,T.;Xie,W.;Geng,S.;Li,R.;Song,S.;Wang,Y.,Constructingoxygenvacancy-regulated cobalt molybdate nanoflakes for efficient oxygenevolution reaction catalysis.Chinese Journal of Catalysis 2022,43(9),2434-2442.

[0091] (4)Zhu,J.;Qian,J.;Peng,X.;Xia,B.;Gao,D.,Etching-induced surfacereconstruction ofNiMoO4 for oxygen evolution reaction.Nano-micro letters2023,15(1),30.

[0092] (5)Cai,Z.;Wang,P.;Zhang,J.;Chen,A.;Zhang,J.;Yan,Y.;Wang,X.,Reinforcedlayereddouble hydroxide oxygen-evolution electrocatalysts:a polyoxometallicacid wet-etching approachand synergistic mechanism.Advanced Materials 2022,34(26),2110696.

[0093] (6) Dalai, N.; Jena, B., Iron nickel sulfide nanorods for oxygen and hydrogen evolution reaction. ChemistrySelect 2023, 8(13), e202204370.

[0094] (7)Choi, S.; Kim, S.-J.; Han, S.; Wang, J.; Kim, J.; Koo, B.; Ryabin, AA; Kunze, S.; Hyun, H.; Han, J., Enhancing Oxygen Evolution Reaction via a SurfaceReconstruction-Induced LatticeOxygen Mechanism.ACS Catalysis 2024,14(20),15096-15107.

[0095] The above embodiments are only preferred implementation modes of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material, characterized in that: The preparation method comprises the following steps: etching the flower-cluster nickel molybdate nanorods synthesized in situ on nickel foam by a one-step hydrothermal synthesis method in a mixed solution of ethanol, water and polyoxometallic acid, washing and drying to obtain a polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material; the polyoxometallic acid comprises phosphotungstic acid and phosphomolybdic acid.

2. The preparation method according to claim 1, characterized in that: The sum of the amounts of phosphotungstic acid and phosphomolybdic acid in 1 L of the mixed solution does not exceed 10 mmol.

3. The preparation method according to claim 1, characterized in that: The volume ratio of the ethanol to water is 1:4 to 4:

1.

4. The preparation method according to claim 1, characterized in that: The etching time is 15 to 90 minutes.

5. The preparation method according to claim 1, characterized in that: The washing specifically includes first washing with anhydrous ethanol for 3 to 5 times, and then washing with deionized water for 3 to 5 times.

6. The preparation method according to claim 1, characterized in that: The drying temperature is 50-60°C.

7. The preparation method according to claim 1, characterized in that: The preparation method of in-situ synthesis of flower cluster-shaped nickel molybdate nanorods on nickel foam by the one-step hydrothermal synthesis method is specifically as follows: block nickel foam is ultrasonically treated in a mixed solution of hydrochloric acid, ethanol and water for 10 minutes, washed with ethanol and pure water for 2 to 3 times respectively, put into a polytetrafluoroethylene reactor containing a mixed solution of ammonium molybdate tetrahydrate and nickel nitrate hexahydrate, and then reacted at 150° C. for 6 hours, cooled to room temperature, washed with ethanol and deionized water for three times respectively, and finally dried at 60° C. for 10 hours to obtain flower cluster-shaped nickel molybdate nanorods.

8. The preparation method according to claim 8, characterized in that: The concentration of hydrochloric acid is 12M, and the volume ratio of hydrochloric acid, ethanol and water is 1:1:

1.

9. The preparation method according to claim 8, characterized in that: The concentration of the ammonium molybdate tetrahydrate is 15 mM, and the concentration of the nickel nitrate hexahydrate is 35 mM.

10. Use of the polyoxometallic acid-etched optimized nickel molybdate oxygen evolution electrocatalytic material obtained by the preparation method according to any one of claims 1 to 9 in electrocatalytic electrolysis of water.

Citation Information

Patent Citations

  • Preparation method of foamed nickel-loaded amorphous phosphorus-doped nickel molybdate bifunctional electrocatalytic electrode and application thereof

    CN111663152A

  • Preparation method of nickel molybdate-based electrode material with rich defect structure

    CN117344338A

Cited By

  • Self-assembled porphyrin cage compound as well as preparation method and application thereof

    CN121537394A